Pemberdayaan Usaha Mikro Produk Rumput Laut - Sekarjati, Kartinasari Ayuhikmatin; Asih, Endang Widuri; Rif`ah, Mega Inayati; Sulistyaningsih, Eka; Emaputra, Andrean; Prasetiyo, Angger Bagus (Jurnal Sains Teknologi dalam Pemberdayaan Masyarakat, 2024)
Based on the program of the Ministry of Maritime Affairs and Fisheries, namely Indonesia, the largest producer of marine and fishery products in 2015, empowerment activities were carried out for the people of Kemadang Village. This was done, because the geographical condition of Kemadang Village is close to Kukup beach, Baron beach and Krakal beach. Natural resources used are sea lettuce (seaweed). These natural resources will be processed into processed food products. However, the people of Kemadang Village have not done marketing well. Therefore, it is necessary to empower the people of Kemadang Village with a marketing mix approach (product, price, place and promotion) to produce a good marketing strategy. The empowerment activity was attended by 40 people from Kemadang Village, of which 72.5% were female and 27.5% were male. To test the level of understanding in this activity, questionnaires were distributed before and after the empowerment activities were carried out. The results obtained are that there are 24-28 people who attend this activity who understand the material presented.